EGMR 13258/18_15500/18_57303/18_9078/20 vom 4. Juli 2023 , CASE OF B.F. AND OTHERS v. SWITZERLAND - Hudoc Ch (2023)
Violation of Article 8 - Right to respect for private and family life (Article 8 - Positive obligations;Article 8-1 - Respect for family life);No violation of Article 8 - Right to respect for private and family life (Article 8 - Positive obligations;Article 8-1 - Respect for family life);No violation of Article 8 - Right to respect for private and family life (Article 8-1 - Respect for family life);Non-pecuniary damage - award (Article 41 - Non-pecuniary damage;Just satisfaction); Violation: 8;8-1; No violation: 8;8-1